Exploring Sound-Motion Similarity in Musical Experience. Issue 3 (2nd July 2016) - Godøy, Rolf Inge; Song, Minho; Nymoen, Kristian; Haugen, Mari Romarheim; Jensenius, Alexander Refsum
Abstract : People tend to perceive many and also salient similarities between musical sound and body motion in musical experience, as can be seen in countless situations of music performance or listening to music, and as has been documented by a number of studies in the past couple of decades. The so-called motor theory of perception has claimed that these similarity relationships are deeply rooted in human cognitive faculties, and that people perceive and make sense of what they hear by mentally simulating the body motion thought to be involved in the making of sound. In this paper, we survey some basic theories of sound-motion similarity in music, and in particular the motor theory perspective. We also present findings regarding sound-motion similarity in musical performance, in dance, in so-called sound-tracing (the spontaneous body motions people produce in tandem with musical sound), and in sonification, all in view of providing a broad basis for understanding sound-motion similarity in music.